lncRNA MIR22HG-Derived miR-22-5p Enhances the Radiosensitivity of Hepatocellular Carcinoma by Increasing Histone Acetylation Through the Inhibition of HDAC2 Activity - Jin, Qiao; Hu, Hao; Yan, Siqi; Jin, Long; Pan, Yuliang; Li, Xiangjun; Peng, Yayi; Cao, Peiguo (Frontiers in Oncology, 2021)
Background With the development of radiotherapy technology, radiotherapyRadiotherapy has been increasingly usedused increasingly to treat primary hepatocellular carcinoma (HCC). However, dueBut due to the radioresistance and the the intolerance of the adjacent organs to radiation, the effects of radiotherapy is are not often unsatisfactory. Therefore, it is necessary to study the radiosensitiszation of in HCC. Method A microarrayMicroarray was used to analyzeanalyse the genes that were significantly gene associated with radiosensitivity. Application of HCC cells, HepG2 and MHCC97H, were subjected to radiation in vitro. Real-time PCR was performed to determine MIR22HG (microRNA22 host gene) and miR-22-5p expression levels., Wwestern blotting wasblot performed to determine histone expression levels. A histone deacetylase (HDAC) whole cell assay was usedsed to determine the activity of HDAC2. Then, MTT, colony formation, 5-ethynyl-2′-deoxyuridineEDU, and wound healing assays were performed to examine the function of MIR22HG and miR-22-5p ion cellular radiosensitivityradiosentivity. Chromatin immunoprecipitationChIP-PCR was used to confirm that HDAC2 affects the acetylation level of the MIR22HG promoter region. Finallyregion.Finally, animal experiments were performed to demonstrate the in vivo effect of MIR22HG on the radiosensitivity of hepatoma in vivo. Results Irradiation can up-regulate MIR22HG expression and down-regulate HDAC2 expression. ;Inhibition of HDAC2 expression promotes histone acetylation in the MIR22HG promoter region and up-regulatesup-regulates MIR22HG expression.; MIR22HG can increase radiosensitivity via miR-22-5p in HCC. Conclusion Inhibition of HDAC2 expression promotes histone acetylation in the MIR22HG promoter region, thereby up-regulating the expression of MIR22HG and promoting the production of miR-22-5p, and ultimately increasing the sensitivity of liver cancer radiotherapy.